Inventario de las plantas de tratamiento de aguas residuales Ejército Nacional de Colombia - Santana Morales, Juan Pablo (Escuela Colombiana de Ingeniería Julio Garavito, 2014)
The National Army of Colombia is one of the largest state-owned companies in the country, so any activity it carries out is reflected in the society that surrounds them. The National Army must comply with environmental regulations, therefore all its treatments wastewater must meet the efficiency required in the discharge permits. Wastewater Treatment Plants - WWTP play a very important role in the protection of the environment, since its design, operation and proper maintenance minimize the risk of contamination of the wastewater. ecosystems used as a source of wastewater.

El Ejército Nacional de Colombia es una de las más grandes empresas estatales que tiene el paÍs, por tanto toda actividad que realice se ve reflejada en la sociedad que los rodea.El Ejército Nacional debe cumplir con la normativa ambiental, por tanto todos sus tratamientos de aguas residuales deben satisfacer la eficiencia requerida en los permisos de vertimiento.Las Plantas de Tratamiento de Agua Residual - PTAR juegan un papel muy importante en la protección del Medio Ambiente, ya que su diseño, funcionamiento y mantenimiento adecuado minimizan el riesgo de contaminación de los ecosistemas utilizados como fuente receptora de aguas residuales.
Keywords: Plantas de Tratamiento de Aguas; Aguas Residuales; Aguas negras; Environmental; Water Treatment Plants